Triangle of Wound Assessment Made Easy: Revisited - Hashim Mohamed; Badriya Al Lenjawi (Dermatology, 2016)
Objective: We have provided evidence based critical review of the “Triangle of wound assessment made easy”. Background: Wound assessment is a vital step in managing patients with acute and chronic wounds in daily clinical practice. The natural progression of most wounds is to heal naturally in a coherent and timely manner, although a minority of wounds will fail to heal. The aim of treating recalcitrant wounds that fail to heal is to control symptoms and delay or prevent complications. One vital step in managing wounds is proper and comprehensive evidence based wound assessment. Methods: We have carried out literature review including systemic reviews, met analysis pertaining wound assessment including international guidelines. Results: We have found few gaps in the proposed “Triangle of wound assessment made easy” which have been addressed accordingly. We have revised the concept of (infection) i.e. “raised white blood cell (WBC) count as a sign of infection” and argued that in up to one-half of patients, even with severe diabetic foot infection raised temperature, WBC count, or sedimentation rate are absent. A second point of concern is the omission of “probing to bone sign” in the diagnostic criteria of local signs of infection. Recent clinical studies have demonstrated that in the presence of a clinically infected ulcer, a positive Probe-to-Bone Test (PTB) test is highly suggestive of osteomyelitis, but a negative test does not rule out the diagnosis; conversely, in the situation of an apparently uninfected foot wound, a positive PTB test is not specific for osteomyelitis, but this diagnosis is unlikely if the PTB test is negative. Lastly, the authors have suggested reducing wound bio burden/manage infection through the use of topical antimicrobial therapy-including antiseptic agents. Topical antiseptics have inconclusive proof of efficacy in various etiology wounds and concern remain regarding their residual cytotoxicity when in contact with newly forming granulating tissues especially when highly concentrated rinse solutions is the common practice in developing countries of the world.